What Does Gen Z See That Can Influence Their Interest In Visiting Indonesia? Study on Instagram @WonderfullIndonesia - Syifa Pramudita Faddila; Agus Rahayu; Heny Hendrayati (International Journal of Economics Development Research (IJEDR), 2024)
Indonesia is one of the countries with the most beautiful tourist destinations in the world. Its beauty must be introduced to all tourists, especially local tourists from the younger generation. This research aims to find out what variables attract the attention of Generation Z when they want to visit tourist attractions, especially after seeing the Instagram account @WonderfullIndonesia. The research involved 180 Generation Z student respondents in Karawang. Data that was collected through a questionnaire distributed using Google Forms was analyzed using SEM-PLS. The research results show that Generation Z's interest in visiting pays attention to eWOM, green marketing, and lifestyle variables. Even though social media marketing activity does not influence visiting interest, it is still a factor that must be considered.